2009
DOI: 10.1211/jpp/61.12.0002
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatics of pharmaceutical inhalation aerosols

Abstract: Objectives This review focuses on the key findings and developments in the rapidly expanding research area of pharmaceutical aerosol electrostatics. Key findings Data from limited in-vivo and computational studies suggest that charges may potentially affect particle deposition in the airways. Charging occurs naturally in the absence of electric fields through triboelectrification, that is contact or friction for solids and flowing or spraying for liquids. Thus, particles and droplets emitted from pulmonary dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Similarly, powder deposition on the walls of the CC can potentially be dislodged easier from capsule‐wall impactions when PTFE coating is used. Considering electrostatic forces, triboelectric charging is known to occur with pharmaceutical powders and is reduced when surfaces of the same material are separated compared with surfaces of different materials . Therefore, coating both the capsule and CC with the same low surface energy material can reduce the buildup of electrostatic charge, which reduces an additional powder retention mechanism and allows the capsule to move more freely in the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, powder deposition on the walls of the CC can potentially be dislodged easier from capsule‐wall impactions when PTFE coating is used. Considering electrostatic forces, triboelectric charging is known to occur with pharmaceutical powders and is reduced when surfaces of the same material are separated compared with surfaces of different materials . Therefore, coating both the capsule and CC with the same low surface energy material can reduce the buildup of electrostatic charge, which reduces an additional powder retention mechanism and allows the capsule to move more freely in the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Although human airways are normally neutral, image charges with equal magnitude and opposite polarity to charged particles may be induced on the surfaces, especially inside small airways in the peripheral lung. (13) Yu (14) derived formulae for deposition fraction due to mutual repulsion in a cylindrical tube as follows:…”
Section: Electrostatic Precipitationmentioning
confidence: 99%
“…Disruption of the electrical double layer in liquid surfaces during atomization also generates spontaneously charged droplets. (13) Particle charges are dependent on many physicochemical parameters, such as formulation composition, device construction, relative humidity, and solid-state properties. This topic is further discussed in the section on particle characteristics.…”
Section: Electrostatic Precipitationmentioning
confidence: 99%
“…Electrostatic charge measurements for pharmaceutical inhalers have revealed high charge levels on the particles emitted from some commercial respiratory drug delivery devices (Byron et al 1997;Kwok et al 2005;Hoe et al 2009;Kwok and Chan 2009). Kwok et al (2005) reported charge levels higher than 40,000 e per particle for particles generated by a commercial metered dose inhaler (MDI).…”
Section: Introductionmentioning
confidence: 99%